Penerapan Konsep Produksi Bersih Ramah Lingkungan Studi Kasus: Industri Pengolahan Tahu - Safitriyawi, Roja; Ilyas, Ilyas; Sentia, Prima Denny; Lestari, Suci Ayu; Ulfah, Tya; Kasmawati, Kasmawati (Jurnal Optimalisasi, 2024)
The tofu industry sector in Aceh is a strategic sector to support the community's economy. In every major production, often found waste in the form of liquid waste and solid waste. Substances contained in tofu waste contain polluted substances in the form of BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand) and TSS (Total Suspendeal Solid). Energy waste also occurs in the equipment used, as well as having an impact seen from economic and environmental aspects. This research was conducted to identify the amount of waste produced in each tofu production process and to provide alternative proposals for improvement of clean production to minimize the amount of waste produced by the PT.X, Banda Aceh. This research was conducted by collecting primary data obtained directly from the company and interviews. Data processing is carried out using mass diagrams to identify waste and the concept of good house keeping clean production, material changes, technological changes, product changes and on-reuse sites. Waste produced in the form of solid waste is 5 grams of spilled soybean and pulp as much as 168 kg, while liquid waste is 109.8 L of water, 15.4 L of scattered water, 953 L of whey and 953 L of vinegar. The results of the identification get as many as 19 problems that will be given a proposal for the implementation of clean production by providing the principle of good house keeping of technological change and site on reuse.